Carthage confronts Dionysius, tyrant of Syracuse - righi, mourad (The Algerian Historical Journal, 2026)
The aim of this study is to examine an important stage in the history of Carthage in its great struggle against the Greeks of Sicily, during the period of the rule of the tyrant Dionysius of Syracuse (405-367 BC), the city that had always declared war on Carthage and its interests on the island, battles took place between them, in which each party mobilized all of its military capabilities and political experience, from the Battle of Gela,To Kabala, the Carthaginian diplomatic experience played an important role in it, whether in terms of its results or in terms of its commitment, contrary to what the tyrant Dionysius appeared to show. Carthage preserved its interests in this conflict, in the face of allied military forces and pens. A Greekism fueled by the spirit of hatred and propaganda for Hellenism from Plato to Diodorus of Sicily.